2014
DOI: 10.1158/1535-7163.mct-13-0918
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Mechanism of Action, and Antitumor Activity of a Small Molecule Inhibitor of Hippo, TGF-β, and Wnt Signaling Pathways

Abstract: Embryonic signaling pathways, in particular those mediated by Wnt and TGF-b, are known to play key roles in tumor progression through the induction of epithelial-mesenchymal transition (EMT). Their simultaneous targeting could therefore represent a desirable anticancer strategy. On the basis of recent findings that both Wnt and TGF-b-associated pathways are regulated by Hippo signaling in mammalian cells, we reasoned that targeting the latter would be more effective in inhibiting EMT. In a search for such inhi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 51 publications
(54 reference statements)
1
43
0
2
Order By: Relevance
“…Therefore, a drug that inhibits YAP/TAZ may have a potent analgesic effect. We have proven that VP, which impedes YAP-TEAD association and inhibits YAP activity (LiuChittenden et al, 2012), is a potent analgesic, supporting the idea that VP, a prescriptive medicine currently used in clinic for treating macular degeneration (Brown et al, 2006), may also be used for treating neuropathic pain. Excitingly, we have further identified a small molecule, dCTB, and shown that it may be the most potent analgesic in treating neuropathic pain.…”
Section: Yap/taz: Potent Analgesic Screening Targetsmentioning
confidence: 64%
See 4 more Smart Citations
“…Therefore, a drug that inhibits YAP/TAZ may have a potent analgesic effect. We have proven that VP, which impedes YAP-TEAD association and inhibits YAP activity (LiuChittenden et al, 2012), is a potent analgesic, supporting the idea that VP, a prescriptive medicine currently used in clinic for treating macular degeneration (Brown et al, 2006), may also be used for treating neuropathic pain. Excitingly, we have further identified a small molecule, dCTB, and shown that it may be the most potent analgesic in treating neuropathic pain.…”
Section: Yap/taz: Potent Analgesic Screening Targetsmentioning
confidence: 64%
“…In the nucleus, TEAD families of transcriptional factors are known to mediate YAP/TAZ activities (Hansen et al, 2015). VP, a prescriptive medicine currently used in the clinical setting for treating macular degeneration (Brown et al, 2006), has the capability of impeding the YAP-TEAD association and causing inhibition of YAP activity (Zhao et al, 2008;Liu-Chittenden et al, 2012). We therefore tested whether VP could impede neuropathic pain.…”
Section: Contributions Of Yap and Taz To The Induction And Maintenancmentioning
confidence: 99%
See 3 more Smart Citations